PENGEMBANGAN MEDIA KOTAK NUSANTARA UNTUK MENINGKATKAN KESADARAN BUDAYA SISWA SEKOLAH DASAR DI KOTA TARAKAN - Suriata, Suriata (Universitas Borneo Tarakan, 2022)
Cultural issues such as stereotypes, discrimination, and microaggressions are prone to occur in intercultural interactions, especially in Tarakan City where people have different cultural backgrounds. If only cultural awareness had been instilled in everyone there would be no more stereotypes, discrimination, and microaggressions that could lead to intercultural conflicts. Education regarding cultural awareness is an important thing that must be given starting from an early age, namely to elementary school students. However, in reality, sources of discussion and learning media regarding cultural awareness are still lacking. For this reason, it is very important to develop learning media that can help foster cultural awareness from an early age in elementary schools. The development of the Kotak Nusantara is a media that can be seen directly by students so that they are more interested, concentrated, and focused on learning objectives. The aim of the research is to develop the Kotak Nusantara in order to increase the cultural awareness of elementary school students in Tarakan City. The research method used is the ADDIE model research and development method which consists of the stages of analyzing, designing, developing, implementing, and evaluating. Based on the research results, from the design validation test and media material, Kotak Nusantara is very suitable for use as a learning medium and can increase the cultural awareness of elementary school students in Tarakan City.Keywords : media, Kotak Nusantara,cultural awareness